The teaching of poetry in the initial training of teachers: Dramatization of poems - Selfa Sastre, Moisés (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The role that poetry occupies in school is generally reduced to recitation of poems on days that commemorate important dates. As teacher trainers at the Faculty of Education of the University of Lleida, in subjects related to the didactics of literature, we intend that our students broaden their view of the poetic genre and conceive it as part of quality literary education. of their future students. The dramatization of poems, as we explain and exemplify here, is a good way to do it to achieve the aforementioned literary education.